Emotional positionung strategy: Can it create customer loyalty in the hardware construction sector in Zimbabwe? - Mupemhi, Ronicah; Mugwati, Miriam; Nkala, Doreen; Machingura, Tsungai (Midlands State University, 2016)
This study seeks to establish the extent to which emotional positioning strategy dimensions may influence customer loyalty in the construction hardware sector in Zimbabwe. The research used both qualitative and quantitative methodology paradigms. Self-administered questionnaires were used to gather data from 300 individual customers. Emotional positioning strategies influence customer loyalty in the construction hardware sector. Emotional positioning strategy (EPS) alone cannot determine the loyalty of customers. There is need to highlight activities of promotion and aspects of economic status as other determinants of loyalty. Improved theoretical models are needed to generate more knowledge about the emotional positioning strategy. The authors believe the findings are particularly relevant for marketing managers of construction hardware. The paper reveals the possible relationships that may exist between emotional positioning strategy techniques and loyalty of customers. The study further suggests some implications for managers when making decisions on adoption and implementation of EPS. The paper identifies a knowledge gap in current position strategies being employed by firms in the construction hardware industry. The original contribution of this paper is to address this gap so that researchers and practitioners have some understanding of the relationship that exists between EPS and loyalty. The framework can also be used by firms in comparable markets.